Arid5a Regulation and the Roles of Arid5a in the Inflammatory Response and Disease - Nyati, Kishan Kumar; Agarwal, Riddhi Girdhar; Sharma, Praveen; Kishimoto, Tadamitsu (Frontiers in Immunology, 2019)
Abnormal gene expression patterns underlie many diseases that represent major public health concerns and robust therapeutic challenges. Posttranscriptional gene regulation by RNA-binding proteins (RBPs) is well recognized, and the biological functions of RBPs have been implicated in many diseases, such as autoimmune diseases, inflammatory diseases, and cancer. However, a complete understanding of the regulation mediated by several RBPs is lacking. During the past few years, a novel role of AT-rich interactive domain-containing protein 5a (Arid5a) as an RBP is being investigated in the field of immunology owing to binding of Arid5a protein to the 3’ untranslated region (UTR) of Il-6 mRNA. Indeed, Arid5a is a dynamic molecule because upon inflammation, it translocates to the cytoplasm and stabilizes a variety of inflammatory mRNA transcripts, including Il-6, Stat3, Ox40, T-bet, and IL-17-induced targets, and contributes to the inflammatory response and a variety of diseases. TLR4-activated NF-κB and MAPK pathways are involved in regulating Arid5a expression from synthesis to degradation, and even a slight alteration in these pathways can lead to intense production of inflammatory molecules, such as IL-6, which may further contribute to the development of inflammatory diseases such as sepsis and experimental autoimmune encephalomyelitis. This review highlights the regulation of the Arid5a expression and function. Additionally, recent findings on Arid5a are discussed to further our understanding of this molecule, which may be a promising therapeutic target for inflammatory diseases.